Observations of interplanetary dust by the Juno magnetometer investigation. Issue 10 (25th May 2017) - Benn, M.; Jorgensen, J. L.; Denver, T.; Brauer, P.; Jorgensen, P. S.; Andersen, A. C.; Connerney, J. E. P.; Oliversen, R.; Bolton, S. J.; Levin, S.
Abstract: One of the Juno magnetometer investigation's star cameras was configured to search for unidentified objects during Juno's transit en route to Jupiter. This camera detects and registers luminous objects to magnitude 8. Objects persisting in more than five consecutive images and moving with an apparent angular rate of between 2 and 18, 000 arcsec/s were recorded. Among the objects detected were a small group of objects tracked briefly in close proximity to the spacecraft. The trajectory of these objects demonstrates that they originated on the Juno spacecraft, evidently excavated by micrometeoroid impacts on the solar arrays. The majority of detections occurred just prior to and shortly after Juno's transit of the asteroid belt. This rather novel detection technique utilizes the Juno spacecraft's prodigious 60 m 2 of solar array as a dust detector and provides valuable information on the distribution and motion of interplanetary (>μm sized) dust. Plain Language Summary: The Juno magnetometer investigation uses star cameras co‐located with the magnetic sensors at the outer end of one of Juno's solar arrays. These cameras compare images with an onboard star catalog to determine the orientation of the sensors in inertial space. They also serendipitously recorded multiple images of small particles excavated from the spacecraft by high‐velocity dust impacts. We trace their trajectories back in time to demonstrate that they evolved from the spacecraft. This allows us to use the vast collecting area of Juno's solar arrays (60 m 2 ) as a novel dust detector, sensitive to particles with a mass range never before measured in situ. Key Points: Star cameras included on the Juno spacecraft payload as part of the magnetometer investigation identified and tracked small objects in close proximity to the spacecraft The tracked objects are identified as submillimeter particles excavated from the spacecraft, liberated by impact of interplanetary dust particles on the spacecraft solar arrays The number and timing of such impacts provide useful information about the distribution, sources, and sinks of interplanetary dust in the solar system.